2017
DOI: 10.1002/anie.201701213
|View full text |Cite
|
Sign up to set email alerts
|

A Metal–Organic Compound as Cathode Material with Superhigh Capacity Achieved by Reversible Cationic and Anionic Redox Chemistry for High‐Energy Sodium‐Ion Batteries

Abstract: Although sodium-ion batteries (SIBs) are considered as alternatives to lithium-ion batteries (LIBs), the electrochemical performances, in particular the energy density, are much lower than LIBs. A metal-organic compound, cuprous 7,7,8,8-tetracyanoquinodimethane (CuTCNQ), is presented as a new kind of cathode material for SIBs. It consists of both cationic (Cu ↔Cu ) and anionic (TCNQ ↔TCNQ ↔ TCNQ ) reversible redox reactions, delivering a discharge capacity as high as 255 mAh g at a current density of 20 mA g .… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
61
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 90 publications
(65 citation statements)
references
References 25 publications
1
61
0
Order By: Relevance
“…Moreover, the transition metal ions participate in the electrochemical reaction at high potentials, which is helpful to raise the battery voltage. In our previous work, we demonstrated a metal–organic compound of CuTCNQ as SIB cathode material showing a very high specific capacity. We found that the cationic Cu + and anionic TCNQ − could simultaneously participate in the redox reaction with a three‐electron transfer process.…”
Section: Figurementioning
confidence: 99%
“…Moreover, the transition metal ions participate in the electrochemical reaction at high potentials, which is helpful to raise the battery voltage. In our previous work, we demonstrated a metal–organic compound of CuTCNQ as SIB cathode material showing a very high specific capacity. We found that the cationic Cu + and anionic TCNQ − could simultaneously participate in the redox reaction with a three‐electron transfer process.…”
Section: Figurementioning
confidence: 99%
“…[1][2][3][4][5][6][7][8][9][10][11] Hitherto, the commercialization of SIBs has been held back, however, by their low energy density and unsatisfactory cycle life. [1][2][3][4][5][6][7][8][9][10][11] Hitherto, the commercialization of SIBs has been held back, however, by their low energy density and unsatisfactory cycle life.…”
mentioning
confidence: 99%
“…The cathodic peaks at 2.35 and 2.15 Vs hift to higherp otential and the integral areas of these peaks along with anodic peak at 3.0 Vs hrink, caused by the dissolution of TCNQ xÀ ,asreported previously. [22,23] An unnoticeable anodicp eak at 1.6 Vi nt he first three scans remains after 100 cycles,w hichm ight be caused by pesudocapacitance similar to Cu-vacancy formed in Cu 2 Ou ltra-small nanocrystals. [34] The cycling performance of Cu-TCNQ/Cu was measured in a voltager ange of 0.01-3.0 Va nd compared with Cu-TCNQ powder ( Figure 3b).…”
Section: Resultsmentioning
confidence: 99%
“…[19][20][21] Recently,asamember of MOFs,Cu-TCNQ has been investigated as ap romising high-capacity cathode materialf or both sodium-ion batteries (SIBs) and potassium-ion batteries (PIBs). [22][23][24][25] Elaborately designed experimentsr eveal that the super high capacity of Cu-TCNQ as cathode materialf or SIBs is contributed by at hree-electron redoxc hemistry in each charge/discharge process between 2.0-4.1 V. Both copper and TCNQ species take parti nt he electrochemical conversion reactions for sodium storage. [23] Although LIBs and SIBs are similar in the redox reactionm echanism, smaller diameterso fL i + ions make LIBs perform distinctively.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation